The role of ethical leadership in instilling values for university leaders: An exploratory study of the opinions of a sample of leaders in Iraqi universities (Entrepreneurship Journal for Finance and Business, 2021)
The current research confirms the importance of promoting ethical behavior and the extent of its impact in anchoring in organizational values and all decisions made by organizations, the ability of the organization to provide sustainable, high-quality services, on the one hand, and the need for the organization’s values to be in line with the ambitious values of employees on the other hand, and the result is high performance. And present behaviors that benefit and do not harm others. Therefore, the research has dealt with two important variables, the first being moral ethcial leadership through its dimensions (justice, integrity, directing behavior, clarity of role, power sharing, concern for sustainability) .As for the second variable, organizational values have adopted the dimensions (quality in values, innovation of values, responsibility for values, and values. Organizational values of customers and organizational values of employees), and the research started from a problem expressed with a number of questions, including whether moral leadership exists among university leaders and can you use positive behaviors and ethical practices to consolidate these organizational values in the universities under study? A intended sample was chosen, represented by (64) members of university leaders who hold senior leadership positions in a number of Iraqi universities that were chosen to implement the study, and the research drew on a number of conclusions, the most prominent of which is that ethical leaders have qualities and characteristics that depend on the social philosophy that relates to the mind, heart and soul. The soul is to be a tool in building a balanced emotional personality, as it searches for means and not ends, as for the most important recommendations for university leaders to pay attention to the sustainability and preservation of relations between employees, seek attention to environmental and technological changes, provide the appropriate organizational climate, follow a work context and take into account the prevailing societal values as a source of intellectual and scientific radiation To reach good performance to support its position in the community, and the continuous urge to adopt professional behavior and interest in building a clear vision that consolidates organizational values in the universities in question